ANALISIS PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KABUPATEN PIDIE JAYA DALAM PERSPEKTIF VAN PETER VAN HORN - Afrijal; Vilzati (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2020)
Analysis of PATEN (District Integrated Administrative Services) aims to determine the extent to which the implementation of policies that are being promoted by related parties in improving public services. This study aims to describe the implementation of PATEN policies in the field of policy analysis in the perspectives put forward by Van Veter and Van Horn. Policy implementation can be done using the Van Metern Van Horn theory which is seen from 6 (six) variables that influence policy implementation, namely; Policy standards and objectives/measures and policy objectives, resources, characteristics of implementing organizations, attitudes of implementers, communication between related organizations and implementation activities and social, economic and political environment. The problems that the implementation of PATEN that wants to be evaluated in Pidie Jaya are the problem of overlapping authority, there are no special PATEN regulations, lack of Human Resources (PNS), unsupported infrastructure, lack of budget to create PATEN implementation, and not optimal PATEN socialization. The results of the analysis show that the implementation of the PATEN policy in Pidie Jaya has been running, but it is still not optimal due to the lack of commitment of PATEN implementers from various parties.